Pengaruh Komunikasi Interpersonal dan Kualitas Pelayanan terhadap Kepuasan Customer pada Hotel Front One Inn Kediri - Rahayu Bella Kartika; Edwin Agus Buniarto; Diana Ambarwati (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
In the era of globalization and rapid technological advancement, business development requires the right strategies to attract customers through customer satisfaction. Therefore, research is needed to uncover whether interpersonal communication and service quality have a partial or simultaneous impact on customer satisfaction. The research was conducted in April 2023, with a sample of 95 respondents, customers of Hotel Front One Inn Kediri. A quantitative descriptive method was used in this research, involving data collection through observation, interviews, and questionnaires. Data analysis in this research included validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The research results indicate that the interpersonal communication of employees with customers and the quality of service provided have a partial impact on Customer Satisfaction at Hotel Front One Inn Kediri. This is shown by the significance value below 0.05. Simultaneously, these variables are known to have an impact on customer satisfaction, with an influence of 27.3%. Hotel Front One Inn Kediri should provide training to its employees on effective communication with customers and how to provide the best service to customers, as it is evident that interpersonal communication and service quality have an impact on customer satisfaction.